Upaya Meningkatkan Hasil Belajar IPAS Siswa Dengan Menggunakan Model Pembelajaran Kooperatif Tipe Student Team Achievement Division (Stad) Di Kelas III SD Negeri 060971 Kemenangan Tani - Rumiris Lumban Gaol; Esmiralda Br Manurung; Yohana Br Silitonga; Miranda Gea; Ria Pepayosa Br Sembiring (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
This research was motivated by the low learning outcomes in Science and Social Studies (IPAS) of third-grade students at SD Negeri 060971 Kemenangan Tani, as indicated by the low level of learning mastery, where only 48.15% of students achieved the Minimum Mastery Criteria (KKM). The low learning outcomes were caused by students’ lack of active participation, teacher-centered learning, and the limited use of innovative learning models. This study aimed to determine the implementation of the Student Team Achievement Division (STAD) cooperative learning model and to improve the IPAS learning outcomes of third-grade students at SD Negeri 060971 Kemenangan Tani in the 2025/2026 academic year. This study employed a Classroom Action Research (CAR) method conducted in two cycles involving 27 students as research subjects. Data were collected through tests, observations, interviews, and documentation. The results showed that the implementation of the STAD cooperative learning model improved students’ learning outcomes. The average score in the Cycle I pretest was 51.85 with 0% classical mastery, increasing to 71.85 with 33.33% classical mastery in the Cycle I posttest, and further increasing to 89.26 with 92.59% classical mastery in Cycle II. In addition, both teacher and student activities improved during the learning process in each cycle. Therefore, it can be concluded that the implementation of the Student Team Achievement Division (STAD) cooperative learning model can improve the IPAS learning outcomes of third-grade students at SD Negeri 060971 Kemenangan Tani in the 2025/2026 academic year.